2019
DOI: 10.21533/pen.v7i4.840
|View full text |Cite
|
Sign up to set email alerts
|

Iraqi e-government and cloud computing development based on unified citizen identification

Abstract: In this paper, besides an overview of e-Government and cloud computing services in Iraq, an applied survey to establish relevant prospects of the Iraqi citizens for e-Government and cloud computing services was adopted. Moreover, to study the potential putting into practice of e-Government and cloud computing services based on citizen identification in Iraq. Based on survey results, 112 different e-Services were proposed by qualified Iraqi citizens. The requested e-Services were highlighted based on a provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Corroborating this, examples of the previously mentioned inhibiting factors have been mentioned as constraining e-government development in some of the fragile states under analysis: "Low populations, large disparities in income and access to on-line services of any sort and low educational levels" in the case of Djibouti (Dolan, 2014); unstable "civil and political conditions" (Abd et al, 2019) and "resistance of some official and nonofficial organizations, groups, and individuals", "delay voting on e-government project that has been submitted to parliament" and "less concern or support shown by politicians and high level government" (Salman, 2019), in the case of Iraq; "technical, infrastructure, cultural and social barriers" (Ahmed et al, 2013) and "lack of studies and researches", "low trust" and "security and privacy concerns" (Murah, and Ali, 2018), in the case of Libya; and cultural and educational factors, income level, lack of trust and "insufficient number of computers and lack of training packages for employees", in the case of Sudan (Elamin and Abushama, 2016).…”
Section: Underperforming Countries 431mentioning
confidence: 83%
“…Corroborating this, examples of the previously mentioned inhibiting factors have been mentioned as constraining e-government development in some of the fragile states under analysis: "Low populations, large disparities in income and access to on-line services of any sort and low educational levels" in the case of Djibouti (Dolan, 2014); unstable "civil and political conditions" (Abd et al, 2019) and "resistance of some official and nonofficial organizations, groups, and individuals", "delay voting on e-government project that has been submitted to parliament" and "less concern or support shown by politicians and high level government" (Salman, 2019), in the case of Iraq; "technical, infrastructure, cultural and social barriers" (Ahmed et al, 2013) and "lack of studies and researches", "low trust" and "security and privacy concerns" (Murah, and Ali, 2018), in the case of Libya; and cultural and educational factors, income level, lack of trust and "insufficient number of computers and lack of training packages for employees", in the case of Sudan (Elamin and Abushama, 2016).…”
Section: Underperforming Countries 431mentioning
confidence: 83%
“…Hence, it was concluded that studies are yet to empirically investigate cloud computing adoption in e-government. From the context of developing countries like Iraq, Abd et al [25] surveyed the relevant prospects of the Iraqi population for cloud computing services and e-Government and found that the qualified Iraqi citizens have proposed 112 different e-services. Hence, this study could be important towards the improvement of e-government services based on cloud computing in Iraq.…”
Section: Discussion Conclusion and Future Research Agendamentioning
confidence: 99%
“…Researchers have recently urged the expansion of the body of knowledge on the advantages and challenges of cloud computing in developing nations, including Iraq. The advantages and difficulties of employing cloud computing services from the viewpoint of users in Iraqi institutions generally [12]. When government organizations choose to implement cloud computing systems, challenges to cloud security are one of their top concerns, but there isn't enough data to support the risks and advantages of security.…”
Section: Cloud In Developing Countriesmentioning
confidence: 99%